1997
DOI: 10.1002/(sici)1097-0134(199710)29:2<203::aid-prot8>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the LAV6 peptide: A nucleation site for the correct receptor-induced refolding of the CD4-binding domain of HIV1 gp 120

Abstract: LAV44 and LAV15 (lymphadenopathy-associated virus) peptides of the CD4-binding region of gp 120 per se bind to the CD4 receptor (Reed and Kinzel, Biochemistry 30: 4521-4528, 1991; Lasky et al., Cell 50:975-985, 1987). Depending on the environment, the LAV peptides exhibit the ability to switch cooperatively between beta-sheet and helical conformation when solvent polarity is changed past a critical point. This property, which is dependent on the amino acid sequence LPCR, is crucial for receptor binding (Reed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 62 publications
(81 reference statements)
0
12
0
Order By: Relevance
“…Earlier NMR investigations on the hexapeptide T L PCRI—containing the original, effective tetrad—have shown that its structure in solution is quite rigid between the Leu and the Arg residues6. On the other hand, the mutant T N PCRI is highly flexible.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Earlier NMR investigations on the hexapeptide T L PCRI—containing the original, effective tetrad—have shown that its structure in solution is quite rigid between the Leu and the Arg residues6. On the other hand, the mutant T N PCRI is highly flexible.…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, preferential φ angles between the Leu2 and Cys 4 displayed values typical for a 3 10 ‐helix. It is thus well suited to form the seed for a series of overlapping turns that—triggered by a particular level of polarity—force the subsequent residues into a conformation that closely resembles a 3 10 ‐helix6. In fact, the existence of a 3 10 ‐helix could be verified for the 15mer in both, NMR measurements and MD simulations4, 7.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…3 There are some unexpected aspects of the MD structure that may be relevant to the mechanism of cooperative refolding in this peptide. The LPCR tetrad at the Nterminus of the peptide has been proposed to function as a nucleation site for the polarity-triggered refolding of the switch domain into a 3 10 helix; it has theoretical potential for forming a reverse turn, it adopts a well-defined turn structure in isolation that is compatible with the angles of a 3 10 helix 25 and, in its absence, no helix is formed. 3 All this would lead one to expect that the model would exhibit a turn centering on these residues.…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that in the inhibitor-complexed model the reverse turn at the N-terminus is centered on the LPCR tetrad, as expected from the 1 H-NMR data, 5,25 rather than on Ile 5 and Lys 6 as in the MD model of the free peptide. The and angles of these last now map to the extended region of the Ramachandran plot (Fig.…”
Section: Resultsmentioning
confidence: 99%